German healthcare professionals' perspective on implementing recommendations about polypharmacy in general practice: a qualitative study - Straßner, Cornelia; Freund, Tobias; Szecsenyi, Joachim; Wensing, Michel (Family practice, 2018)
BackgroundKey recommendations for the management of patients with polypharmacy are structured medication counselling (SMC), medication lists and systematic medication reviews.ObjectiveThe aim of this study was to identify determinants (hindering and facilitating factors) for the implementation of the recommendations in general practice.MethodsThis study was linked to a tailored intervention aimed at improving the implementation of the recommendations in German general practice. Interviews and focus groups with different healthcare professionals were carried out in the design phase and after delivery of the intervention. The material from both data collections was analysed separately in a content analytical approach resulting in two sets of categories. For this study, the subcategories of both sets were assigned to the Tailoring Interventions for Chronic Diseases (TICD) checklist, a comprehensive framework of determinants of practice.ResultsInterviews with 24 general practitioners (GPs), 4 other medical specialists, 1 pharmacist, 3 nurses and 6 medical assistants as well as 2 mixed focus groups with 17 professionals were conducted. We identified 93 determinants: 29 referred to medication counselling, 21 to the use of medication lists, 20 to medications reviews and 23 to all recommendations. The determinants were related to all 7 main domains and to 25 of the 57 subdomains on the TICD checklist including guideline factors, patient factors, individual healthcare professional factors, social, political and legal factors, incentives and resources, and capacity for organizational change.ConclusionWhile many interventions to improve polypharmacy focus on the provision of pharmacological knowledge, a much wider range of domains need to be addressed, such as communication skills, patient involvement and practice organization.
Advance access publication 16 December 2017
Gesehen am 26.08.2020